2008
DOI: 10.1101/gr.080945.108
|View full text |Cite
|
Sign up to set email alerts
|

Defensins and the dynamic genome: What we can learn from structural variation at human chromosome band 8p23.1

Abstract: Over the past four years, genome-wide studies have uncovered numerous examples of structural variation in the human genome. This includes structural variation that changes copy number, such as deletion and duplication, and structural variation that does not change copy number, such as orientation and positional polymorphism. One region that contains all these types of variation spans the chromosome band 8p23.1. This region has been studied in some depth, and the focus of this review is to examine our current u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 110 publications
(133 reference statements)
2
82
0
1
Order By: Relevance
“…[6][7][8][9]43,44 The copy numbers of different types of defensin and olfactory receptor genes in the REPD and REPP regions are highly variable, leading to cytogenetically visible euchromatic variants if the copies are sufficiently high. 4,45,46 However, these euchromatic variants are indistinguishable from the genuine 8p23.1 duplication under a light microscope. For example, two of the three patients with 8p23.1 duplication in this study were initially reported as euchromatic variants to the referring physicians.…”
Section: P231 Duplicationmentioning
confidence: 85%
See 4 more Smart Citations
“…[6][7][8][9]43,44 The copy numbers of different types of defensin and olfactory receptor genes in the REPD and REPP regions are highly variable, leading to cytogenetically visible euchromatic variants if the copies are sufficiently high. 4,45,46 However, these euchromatic variants are indistinguishable from the genuine 8p23.1 duplication under a light microscope. For example, two of the three patients with 8p23.1 duplication in this study were initially reported as euchromatic variants to the referring physicians.…”
Section: P231 Duplicationmentioning
confidence: 85%
“…Three mechanisms may explain the origin of inv dup del(8p) (Figure 3) with detailed explanations referred to the recent reports. 4,8,24,34 In brief, all three mechanisms involve the formation of a dicentric chromosome 8 (dic(8)) in meiosis I followed by breakage of the dic(8) either during meiotic division or during early stages of embryonic development leading to the production of an inv dup del(8p). However, the events causing the formation of a dic (8) differ among the three mechanisms.…”
Section: Repd and Repp-mediated Inv Dup Del(8p)mentioning
confidence: 99%
See 3 more Smart Citations